2012
DOI: 10.1007/s00106-012-2526-x
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular dysfunction after cochlear implant in adults

Abstract: Using the described techniques and materials, the risk of loss of vestibular function and the incidence of clinical vertigo can be minimized. Postoperative vertigo did not occur more often in patients with preoperative diminished vestibular function than in patients with normal findings. Therefore, preoperative vestibular function tests cannot be an indicator for the frequency of vertigo after CI. If one vestibular organ shows preoperative dysfunction, the non-affected normal vestibular organ should not be imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 23 publications
0
16
0
2
Order By: Relevance
“…Subgroup Analysis. The sub-meta-analyses for both surgical insertion techniques cochleostomy and RW approach showed comparable results investigating nystagmography (cochleostomy: fixed effect model, OR of 0.22; 95% CI 0.09-0.54; P 5 0.0010 9,20,26,27,53,74,[81][82][83][84] and RW approach: random effects model, OR of 0.23; 95% CI 0.07-0.74; P 5 0.0136 15,20,52,75,79,81,85,86 ) and VEMPs (cochleostomy: fixed effect model; OR of 0.08; 95% CI 0.024-0.25; P 5 0.0001 9,12,32,74,78,80 and RW approach: fixed effect model, OR of 0.09; 95% CI 0.02-0.36; P 5 0.0008 8,15,52,75,79 ), compared to the whole meta-analyses with the complete data set. The OR and CI were essentially unaltered compared with the whole meta-analyses.…”
Section: Subgroup Analysis Sensitivity Analysis Publication Bias Amentioning
confidence: 86%
See 4 more Smart Citations
“…Subgroup Analysis. The sub-meta-analyses for both surgical insertion techniques cochleostomy and RW approach showed comparable results investigating nystagmography (cochleostomy: fixed effect model, OR of 0.22; 95% CI 0.09-0.54; P 5 0.0010 9,20,26,27,53,74,[81][82][83][84] and RW approach: random effects model, OR of 0.23; 95% CI 0.07-0.74; P 5 0.0136 15,20,52,75,79,81,85,86 ) and VEMPs (cochleostomy: fixed effect model; OR of 0.08; 95% CI 0.024-0.25; P 5 0.0001 9,12,32,74,78,80 and RW approach: fixed effect model, OR of 0.09; 95% CI 0.02-0.36; P 5 0.0008 8,15,52,75,79 ), compared to the whole meta-analyses with the complete data set. The OR and CI were essentially unaltered compared with the whole meta-analyses.…”
Section: Subgroup Analysis Sensitivity Analysis Publication Bias Amentioning
confidence: 86%
“…Two patients complained about new onset of sway vertigo. Additionally, six studies reported on altered quality of vertigo, [19][20][21]23,28,29 whereas five studies did not observe any change in vertigo quality 17,24,26,27,30 (altered vertigo in 11.6%, 77 of 663 patients). In this subgroup of studies, 19.5% (129 of 663 patients) complained about new onset of vertigo after cochlear implantation.…”
Section: Vertigo Qualitymentioning
confidence: 94%
See 3 more Smart Citations